Green synthesis of copper oxide nanoparticles using the Bombax ceiba plant: Biodiesel production and nano-additive to investigate diesel engine performance-emission characteristics. (1st July 2023) - Arun, S.B; Karthik, B.M; Yatish, K.V; Prashanth, K.N; Balakrishna, Geetha R.
Abstract: In this study, Bombax ceiba plant components, such as flowers and seeds, are successfully exploited as green sources in order to synthesize copper oxide nanoparticles (CuO NPs) and generate biodiesel. B. ceiba flower extract is used as a fuel-cum-reducing source for the CuO NPs synthesis through the solution combustion method. The CuO NPs were characterized through BET, FTIR, TEM, XRD, and FESEM. Particularly, the produced CuO NPs are utilized as reusable heterogeneous catalysts in the synthesis of biodiesel using a feedstock of B. ceiba oil. The maximum 95.6% biodiesel/ Bombax ceiba methyl ester (BCME) is achieved at 3.5 wt% CuO NPs concentration, 60 °C temperature, an 11:1 methanol to oil (M/O) molar ratio, and a 50-min reaction time. The CuO NPs demonstrated good reusability through a negligible loss of biodiesel yield. The BCME production is consistent with a pseudo-first order reaction, with a 43.74 kJ/mol of activation energy (Ea) and 1.7 × 10 5 min −1 of frequency factor (A). The synthesized biodiesel is characterized through FTIR, and the fuel characteristics were estimated consistent with the ASTM 6751 standards. The metrics of green chemistry were also estimated. Further, the CuO NPs obtained through the green method are used as additives in diesel engines to study the performance and emission characteristics of the BCME diesel blend (BCME20). The CuO NPs were dispersed into the BCME-20 at varying concentrations of 50 ppm and 100 ppm. The results revealed that the brake thermal efficiency of BCME20CuO100 fuel is 2.5% higher than that of BCME20, and the reduction in BSFC is 8.3%. The engine emissions, such as HC (36.35%) and CO (43.90%) were considerably lowered when compared to BCME-20. The NOx emission of BCME20CuO100 is 5.94% lower than BCME20 and higher than diesel fuel. Further, the smoke emissions obtained for diesel, BCME20, BCME20CuO50, and BCME20CuO100 are 31%, 28%, 23%, and 18%, respectively. Graphical abstract: Image 1 Highlights: Reporting novel green synthesized CuO NPs from Bombax ceiba flowers. A maximum 95.4% biodiesel yield obtained using B. ceiba oil. Detailed comparative between diesel, BCME20 Blends with CuO NPs dispersion. BCME20CuO100 showed significant results compared to diesel and BCME20. Decreased harmful engine emissions like NOx, CO, and HC.